Oral fluid as a material for serological diagnostics of caseous lymphadenitis in goats - Kinga Biernacka; Marcin Mickiewicz; Zofia Nowek; Agata Moroz-Fik; Magdalena Rzewuska; Ewelina Kwiecień; Małgorzata Murawska; Tomasz Nalbert; Olga Szaluś-Jordanow; Lucjan Witkowski; Iwona Markowska-Daniel; Emilia Bagnicka; et al. (Scientific Reports)
Abstract Corynebacterium pseudotuberculosis causes caseous lymphadenitis (CLA) in goats and sheep. This study assessed oral fluid (OF) as a minimally invasive sample for CLA serodiagnosis by detecting antibodies to phospholipase D (PLD), CP40 protein, and protein kinase G (PknG) using Western blot (WB). Serum and OF samples from 96 goats from a CLA-affected herd in Poland were tested using a commercial ELISA coated with recombinant PLD (rPLD-ELISA; serum only) and WB (serum and OF). Depending on the cut-off, the rPLD-ELISA had 70–80% diagnostic sensitivity. WB on serum showed very high diagnostic sensitivity (98%) and good agreement with the rPLD-ELISA. WB on OF was highly consistent with WB on serum, however it had slightly lower diagnostic sensitivity (90%). Moreover, WB on OF showed substantial variations in antigen detection, with antibodies to PLD being most effectively detected. Considerably fewer OF samples had anti-CP40 and PknG antibodies, likely due to antibody class variations or detection limitations. Further investigation into immunoglobulin classes in different sample types and optimized secondary antibodies is essential for developing an effective OF-based diagnostic test for CLA.